Enterococcal Bacteremia in Children With Malignancies and Following Hematopoietic Stem Cell Transplantation: A 15-Year Single-Center Experience. Issue 4 (April 2020) - Friedman, Gal; Stepensky, Polina; Abu Ahmad, Wiessam; Masarwa, Reem; Temper, Violetta; Oster, Yonatan; Amit, Sharon; Averbuch, Diana
Abstract : Background: Data on enterococcal bacteremia (EB) in immunocompromised children are scarce. We aimed to describe EB in children with hematologic malignancies (HM), solid tumors and/or following allogeneic hematopoietic stem cell transplantation (HSCT) and analyze their ampicillin and vancomycin resistance. Methods: We conducted an observational retrospective study in the tertiary-care Hadassah University Medical Center (2001-2015). We collected demographic, clinical and laboratory data on EB and compared ampicillin and vancomycin sensitive with resistant episodes. Results: Fifty-six of 1123 children developed 74 episodes of EB; 62.1% Enterococcus faecium, 36.5% Enterococcus faecalis ; and 1.4% Enterococcus gallinarum . EB developed in 12.1% of HSCT patients, 5.1% of HM, 6.3% of neuroblastoma and 1.0% of other solid tumors patients. Of these episodes, 85.1% were nosocomial, and 71.6% developed while on antibiotic therapy. Resistance rates were: to ampicillin, 57.6%; to vancomycin (vancomycin-resistant enterococci), 21.6%; and higher rates among E. faecium . Among vancomycin-resistant enterococci, 1 of 16 was linezolid and 2 of 10 daptomycin resistant. Overall 7- and 30-day mortality rates were 2.7% and 5.4%, respectively. Thirty-day mortality was 18.2% in recurrent episodes and 0% in the first-time EB episodes ( P = 0.006). In multivariate analysis, high treatment intensity was associated with ampicillin resistance [odds ratio (OR) = 3.18, 95% confidence interval (CI): 1.31–9.12], prior penicillin exposure (OR = 7.50, 95% CI: 1.41–39.81) and breakthrough on vancomycin (OR = 18.83, 95% CI: 3.31–101.14) with vancomycin resistance. Conclusions: EB occurs mainly as a nosocomial infection in children receiving high-intensity chemotherapy, especially in those with neuroblastoma, HM and following HSCT. Antibiotic resistance is common. Vancomycin resistance can occur regardless of previous vancomycin use. Prognosis in immunocompromised children with EB is better than previously reported. Recurrent EB is associated with increased mortality.